Cambodia achieved a high vaccination coverage for its population: a good example of a lower middle-income country$aNgoc Phuong Hong Tao, Dang Nguyen, Le Huu Nhat Minh, Veasna Duong, Chey Beaupha, Tareq AL-Ahdal, Nguyen Tien Huy - Ngoc Phuong Hong Tao; Nguyen, Dang; Nhat Minh Le Huu; Duong, Veasna; Beaupha, Chey; Al-Ahdal, Tareq; Nguyen Tien Huy (Journal of global health, 2022)
The COVID-19 global epidemic is a major catastrophe with disastrous negative health effects on the economy and society. Vaccination is a straightforward, effective, and risk-free option for guarding against COVID-19. Governments of many countries have implemented strategies in managing hazards and vaccination recommendations for their citizens. Gavi’s COVID-19 Vaccines Global Access (COVAX) Advance Market Commitment (AMC) provided access to COVID-19 vaccinations to more than 90 countries, including low-income countries like Cambodia. The effective integration of vaccines in Cambodia has resulted in the saving of lives, the consolidation of the health care system, and a contribution to national progress toward economic recovery.